Thoracic Paravertebral Block and Its Effects on Chronic Pain and Health-Related Quality of Life After Modified Radical Mastectomy. Issue 4 (1st July 2014) - Karmakar, Manoj Kumar; Samy, Winnie; Li, Jia W.; Lee, Anna; Chan, Wing Cheong; Chen, Phoon P.; Ho, Anthony M.-H.
Abstract : Background and Objectives: Patients undergoing breast cancer surgery frequently experience chronic postoperative pain. The primary objective of this randomized study was to determine if thoracic paravertebral block (TPVB) reduced the incidence of chronic pain after a modified radical mastectomy (MRM) when compared with general anesthesia (GA). Methods: One hundred eighty women undergoing MRM were randomized to 1 of 3 study groups: group 1: standardized GA, group 2: GA with a single-injection TPVB and placebo paravertebral infusion, and group 3: GA with a continuous TPVB. Outcomes assessed postoperatively included acute postoperative pain and analgesic consumption and, at 3 and 6 months, the incidence and severity of chronic pain and physical and mental health-related quality of life (HRQOL). Results: There was no significant difference in the incidence of chronic pain at 3 months ( P = 0.13) and 6 months ( P = 0.79) after the MRM between the study groups. The relative risk of developing chronic pain ( P = 0.25) was also similar between the groups. There was no difference in acute pain ( P = 0.22) or postoperative analgesic consumption ( P = 0.67) between the groups. Nevertheless, differences were observed in chronic pain–related secondary outcome variables. The TPVB groups reported lower chronic pain scores ( P < 0.05), exhibited fewer symptoms and signs of chronic pain ( P ⩽ 0.01), and also experienced better physical and mental HRQOL than did the GA group. Chronic pain scores also decreased with time in all study groups ( P < 0.05). Conclusions: There is no significant difference in the incidence or relative risk of chronic pain at 3 and 6 months after an MRM when TPVB is used in conjunction with GA. Nevertheless, patients who receive a TPVB report less severe chronic pain, exhibit fewer symptoms and signs of chronic pain, and also experience better physical and mental HRQOL.